Chemistry for the IB Diploma - Talbot, Christopher, 1967-; Davison, Chris (Christopher); International Baccalaureate (Foundation) (London : Hodder Education, an Hachette UK Company, 2023)
A chemistry textbook that contains all Standard Level and Higher Level content for the IB Diploma and features exam-style questions and questions from past papers.
"In cooperation with IB"--Front cover.
Includes index.
Young Adult
Young Adult
Keywords: Chemistry -- Textbooks; Chemistry -- Examinations -- Study guides; Chemistry -- Study and teaching (Secondary); International baccalaureate -- Study guides; Chemistry -- Textbooks; Chemistry -- Examinations -- Study guides; Chemistry -- Study and teaching; International baccalaureate -- Study guides; Study guides; Textbooks